Ensaio sobre a revisão da oralidade - Paula Taveira; Santos, Diana (Revista da Associação Portuguesa de Linguística, 2016)
This paper discusses the revision of the transcription of oral interviews done by the Portuguese Museu da Pessoa to preserve the life histories of common people, often with little or no formal education, which had been transcribed by students without linguistic training. This task increased our awareness of how orality works and of how many choices a transcriber is required to make, being a sort of translator. In addition, it uncovered a set of «errors» or deviations in many elderly speakers from the North of Portugal which are often considered typically Brazilian, leading us to reconsider variety divergence.